Design and performance optimization of a novel lens antenna for emerging beyond 5G wireless applications - Zhang, Jinhua; Dong, Shi; Alsekait, Deema Mohammed; Khan, Imran; Wang, Pi-Chung; Hameed, Ibrahim A. (Frontiers in Materials, 2024)
This paper proposes a novel all-dielectric design of lens antenna and its performance is optimized using genetic algorithm (GA). The optimization objective are 1-dB and steady gain that are directly optimized. The GA also optimizes the topological design of the lens. The method consists of two main components: the design of the objective function and the initial population selection. The first lens structure fed into the algorithm and the initial population match. The lens has a diameter of 150 mm and a thickness of 30 mm at its thickest point with working frequency of 6 to 18 GHz. The 3D printing technology is used for the antenna fabrication that reduces the implantation cost. The experimental results show that the gain and peak aperture efficiency of the proposed antenna are 23.8 dBi and 51.9%, respectively, better than those of the existing designs. It advantages are low-cost, easy to fabricate, simple design, high gain, narrow beams, low side lobes. It can be used in future ultra-wideband (UWB) applications.